Is late‐onset Alzheimer's disease really a disease of midlife?. Issue 2 (25th July 2015) - Ritchie, Karen; Ritchie, Craig W.; Yaffe, Kristine; Skoog, Ingmar; Scarmeas, Nikolaos
Abstract: Introduction: Increasing evidence suggests that Alzheimer's disease (AD) may begin decades before evidence of dementia, indicating that it may be a disorder of midlife rather than old age. Methods: In the absence of long‐term prospective studies from early adulthood specifically designed to address this question, a group of international experts examined evidence presently available from previous clinical and population studies to provide an evidence‐based opinion as to whether such a change in conceptualization may be justified. Results: Although still lacking confirmation from dedicated prospective biomarker studies, there is already considerable evidence to suggest both risk factor exposure and brain changes may be already present in midlife. Discussion: Current evidence suggests (1) that a change in clinical approach notably involving promotion of cardiovascular health in persons with a family history of AD may considerably reduce disease risk and (2) that the development of biomarkers at this early stage will lead to the possibility of clinical trials at a much earlier stage.